A new member of the MCM protein family encoded by the human MCM8 gene, located contrapodal to GCD10 at chromosome band 20p12.3–13 - Johnson, Edward M. (Oxford University Press, 2003)
The MCM8 protein from HeLa cells, a new member of the MCM family, co-isolates through several steps with MCM6 and MCM7, and MCM8 co-immunoprecipitates with MCM4, MCM6 and MCM7, proteins reportedly forming a helicase complex involved in initiation of DNA replication. MCM8 mRNA is expressed in placenta, lung and liver, but is also significantly expressed in adult heart, a tissue with a low percentage of proliferating cells. The MCM8 gene, consisting of 19 exons, is located contrapodal to a gene, consisting of 11 exons, encoding a homolog of the yeast GCD10 gene product. The region between these two transcription units, comprising as few as 62 bp, is TATA-less and highly GC-rich, containing multiple CpG units. MCM8 expression is altered in certain forms of neoplasia. In a case of choriocarcinoma MCM8 mRNA is aberrant, leading to expression of a protein lacking 16 amino acids. In several cases of colon adenocarcinoma MCM8 expression is greatly reduced relative to matched non-cancerous tissue. The potential helicase domain of MCM8 is different from those of other MCM proteins in that it is more homologous to canonical ATP-binding domains of other known helicases. Results suggest that MCM8 may interact with other MCM proteins to alter the function of the replicative MCM protein complex.